2013
DOI: 10.1371/journal.pone.0056780
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Screens for Proteins That Interact with the Mucolipidosis Type IV Protein TRPML1

Abstract: Mucolipidosis type IV is a lysosomal storage disorder resulting from mutations in the MCOLN1 gene, which encodes the endosomal/lysosomal Transient Receptor Potential channel protein mucolipin-1/TRPML1. Cells isolated from Mucolipidosis type IV patients and grown in vitro and in in vivo models of this disease both show several lysosome-associated defects. However, it is still unclear how TRPML1 regulates the transport steps implicated by these defects. Identifying proteins that associate with TRPML1 will facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…TRPML1 also associates with members of the lysosome-associated protein transmembrane family, which is important for the organelle remodeling (Spooner et al, 2013). TRPML1 might be also coupled to transducer of regulated CREB activity-1, which supports a role in organelle fusion (Venkatachalam et al, 2013).…”
Section: +mentioning
confidence: 99%
“…TRPML1 also associates with members of the lysosome-associated protein transmembrane family, which is important for the organelle remodeling (Spooner et al, 2013). TRPML1 might be also coupled to transducer of regulated CREB activity-1, which supports a role in organelle fusion (Venkatachalam et al, 2013).…”
Section: +mentioning
confidence: 99%
“…Indeed, unbiased protein interaction studies have found that TRPML1 physically interacts with several mitochondrial proteins [127]. Therefore, lysosomal dysfunction in cells lacking TRPML1 lead to concomitant aberrations in mitochondrial function, morphology, Ca 2+ buffering capacity, and caspase-mediated cell death [128].…”
Section: Biological Functions Of Trpmlsmentioning
confidence: 99%
“…A large-scale screen identified several candidate proteins that interact with TRPML1 [127]. Briefly, some of the interesting interactors of TRPML1 in this screen involved the cytoskeleton modifying small G-proteins such as Rac2 and Cdc42 (indicating a potential role of TRPML1 in cytoskeleton regulation), lysosomal enzymes such as Cathepsin B, members of the solute carrier family of transporters, the ER Ca 2+ release channel IP 3 -receptor as well as the Ca 2+ transporting ATPase (SERCA2), markers of the ER-Golgi intermediate compartments (ERGIC) and Yif1, which regulate ER to Golgi trafficking of proteins (these interactions may mediate the exit of TRPML1 and associated proteins from the ER), and peroxisome-associated Pex16 [127].…”
Section: Physical and Genetic Interactors Of Trpmlsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, TRPML1 has been characterized using electrophysiological tools and its basic cation channel properties have been investigated [9][10][11][12][13][14][15][16][17][18][19] , its protein-protein interaction network has been explored [20][21][22][23][24] , and knockout mouse models have been generated and investigated [25][26][27][28] . However, effective treatment options for MLIV patients are still missing.…”
mentioning
confidence: 99%